If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + 1) = (6y + -25) Reorder the terms: (1 + 5y) = (6y + -25) Remove parenthesis around (1 + 5y) 1 + 5y = (6y + -25) Reorder the terms: 1 + 5y = (-25 + 6y) Remove parenthesis around (-25 + 6y) 1 + 5y = -25 + 6y Solving 1 + 5y = -25 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 1 + 5y + -6y = -25 + 6y + -6y Combine like terms: 5y + -6y = -1y 1 + -1y = -25 + 6y + -6y Combine like terms: 6y + -6y = 0 1 + -1y = -25 + 0 1 + -1y = -25 Add '-1' to each side of the equation. 1 + -1 + -1y = -25 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = -25 + -1 -1y = -25 + -1 Combine like terms: -25 + -1 = -26 -1y = -26 Divide each side by '-1'. y = 26 Simplifying y = 26
| -20=-3(x-1)+7(x-5) | | 1.04v^2-2.88v=0 | | 5.7x-2.5=7-3.3x | | 6x+9(x-8)=3(x+6)-90 | | 7(3f+6)-f= | | 7x-4+x=-1+13x+7 | | 5x-40=7+-1x | | T-9a+4=112 | | 0=6x^2+23x+15 | | 7(y-3)+9(y+1)=20 | | t+2t+t+t= | | 24x^2-12y^3+8y^2=0 | | 5.75+3x=10.60714285714286+2x+1.142857142857143 | | N-1/7n=18 | | ry=2x-5forx | | -y+4x-(x-6y)= | | -5(3x+2)+6x=17 | | 3x+2+x+10= | | (9x)=(7x+3) | | 3+8v-10v=21 | | 4*4*4=y | | (4x+8)*3=180 | | 0=4x^2+13x+10 | | P-165=321 | | -1.2x^3+10.8x^2-8x=0 | | 4*3=y | | 1=6(0)+b | | k+24=9k | | 20=6w+2.30 | | 72=v/4 | | 0y-1=15-6y+4y | | 4(3)=y |